Stormy night - Wasserman, Robin; Duendes del Sur (Firm); Cartoon Network (Television network) (New York : Scholastic, 2003)
Young readers may use the picture clues to help Scooby-Doo and Shaggy figure out whether their house is haunted.
At head of title: Cartoon Network.
"Cartoon Network."
"WB Worldwide Publishing."
"Preschool-grade 1"--Cover p. [4]
1.4
Keywords: Dogs -- Fiction; Monsters -- Fiction; Haunted houses -- Fiction; Mystery and detective stories; Rebuses